DOES REPEATED PRACTICE MAKE PERFECT? THE EFFECTS OF WITHIN-SESSION REPEATED RETRIEVAL ON SECOND LANGUAGE VOCABULARY LEARNING - Nakata, Tatsuya (Studies in second language acquisition, 2017)
Although research shows that repetition increases second language vocabulary learning, only several studies have examined the long-term effects of increasing retrieval frequency in one learning session. With this in mind, the present study examined the effects of within-session repeated retrieval on vocabulary learning. The study is original in that it (a) gave posttests after a delay greater than 2 weeks, (b) employed a paired-associate format to exert strict control over the treatment, (c) considered time-on-task as a factor, and (d) used the same target items for different frequency levels. In this study, 98 Japanese learners studied 16 English-Japanese word pairs using one of the following four retrieval frequency levels: one, three, five, or seven. Results showed that five and seven retrievals contributed to significantly higher scores than one and three retrievals regardless of the posttest timing. When time-on-task was controlled, however, one retrieval led to the largest gain.